Reliable Multicasting Service for Densely Deployed Military Sensor Networks. (25th August 2015) - Na, Woongsoo; Dao, Nhu-Ngoc; Cho, Sungrae
Wireless sensor networks (WSNs) have drawn attention for military applications where a large number of light-weight sensor nodes can detect enemies and intruders in the battlefield and alert a command post (CP) to our forces. In particular, in the military sensor networks, QoS (quality-of-service) is one of the most important requirements to support their mission-critical applications. However, achieving reliable data transmission is not an easy task because sensor nodes are densely deployed and wireless channel is unpredictable due to high mobility. Also, in the multihop deployed sensor networks, redundant data forwarding occurs frequently and it causes interference among the nodes. In this paper, we propose an efficient reliable multicast scheme using pre-ACK frames to provide fully reliable multicasting and decrease unnecessary data forwarding in the military sensor networks. When a receiver node overhears a multicast frame, the pre-ACK is used to announce its reception of the multicast frame to neighboring nodes which then do not need to duplicate the same multicast frame to it. The performance evaluation shows that the proposed scheme provides full reliability (100%) and outperforms the existing schemes in terms of aggregate throughput (612%) and energy consumption (514%) when the number of nodes is 512 with full buffer.